Risk Factors for Gallbladder Stone Formation after Gastric Cancer Surgery - Lee, Young-Won (J Gastric Cancer, 2019)
PURPOSE: Although an increased incidence of gallbladder (GB) stone formation after gastrectomy has been reported, its etiology remains uncertain. The goal of this study was to explore the incidence of gallstone formation after gastrectomy in gastric cancer patients and investigate the risk factors therein. MATERIALS AND METHODS: Medical records of patients who underwent curative gastrectomy, performed by a single surgeon between August 2012 and December 2015 at the Asan Medical Center, were retrospectively reviewed. Baseline characteristics and surgical outcomes, including GB stone gallstone formation after gastrectomy, were analyzed. RESULTS: Of 561 patients included in the study, 36 presented with GB stone formation after gastrectomy for gastric cancer. The incidence of gallstone formation was 6.4%. The mean interval between gallstone formation and gastrectomy was 21.9 months. In multivariate analyses, the incidence of gallstone formation increased in patients 63 years or older, with greater than 6.2 kg weight loss in the first 6 months after the procedure, a preoperative serum total bilirubin level greater than 0.5 mg/dL, and in patients who did not receive adjuvant chemotherapy. CONCLUSIONS: This study presented risk factors for GB stone formation after gastric cancer surgery, and special attention should be afforded to patients with such risk factors.